Adjunctive Nd:YAG Laser Irradiation for Ridge Preservation and Immediate Implant Procedures: A Consecutive Case Series. Issue 3 (10th April 2019) - Choi, Alicia Y.; Reddy, Caitlin M.; McGary, Ryan T.; Hill, Richard B.; Swenson, Dane T.; Seibel, Paul; Hoag, Justin M.; Berridge, Joshua P.; Johnson, Thomas M.
Abstract : Introduction: Whether or not laser use provides any meaningful benefit at immediate implant and ridge preservation sites remains an open question in periodontics. However, various lasers have been used in conjunction with tooth extraction and immediate implant placement. Evidence supporting adjunctive laser irradiation at immediate implant and ridge preservation sites is mostly limited to preclinical studies and a small number of case reports. Case Series: Adjunctive neodymium‒doped: yttrium, aluminum, garnet (Nd:YAG) laser irradiation was used at six immediate implant sites and five ridge preservation sites. Three immediate implants were in maxillary incisor positions and three were in premolar positions, two maxillary and one mandibular. All cases exhibited favorable healing and satisfactory clinical outcomes. Conclusions: Nd:YAG laser energy application with 650‐µs pulse duration consistently supported rapid clot formation and graft containment at immediate implant and ridge preservation sites. Histologic analyses and controlled clinical trials comparing ridge preservation and immediate implant procedures with and without laser use are needed. Because cellular responses and clinical outcomes may be exquisitely sensitive to irradiation parameters, studies should report materials and methods in detail.